Determination of histamine in fish by Surface Enhanced Raman Spectroscopy using silver colloid SERS substrates. (1st June 2017) - Janči, Tibor; Valinger, Davor; Gajdoš Kljusurić, Jasenka; Mikac, Lara; Vidaček, Sanja; Ivanda, Mile
Highlights: Rapid and sensitive method of histamine determination in fresh fish. Based on simple and low cost SERS substrate. Sample preparation approximately 30 min. Reliable PLS model in concentration range from 0 to 200 mg kg −1 (R 2 pred  = 0.962, RPD = 7.250). Abstract: This study was focused on development of a rapid and sensitive method for histamine determination in fish based on Surface Enhanced Raman Spectroscopy (SERS) using simple and widely available silver colloid SERS substrate. Extraction of histamine with 0.4 M perchloric acid and purification with 1-butanol significantly shortened sample preparation (30 min) and provided clear SERS spectra with characteristic Raman bands of histamine. Principal component analysis effectively distinguished SERS spectra of fish samples with different histamine content. Partial least square (PLS) regression models confirmed reliability of detection and spectral analysis of histamine with SERS. In histamine concentration range 0–200 mg kg −1, significant in legislative and fish quality control aspects, PLS regression model based on spectral range 1139.9–1643.7 cm −1 showed linear trend with R 2 pred  = 0.962, RPD = 7.250. Presented protocol for histamine extraction and purification followed by SERS analysis coupled with chemometric approach, enabled development of rapid and inexpensive method for histamine determination in fish.